CABLE-DRIVEN ROBOT SYSTEM FOR OPERATION INSIDE LONG PILES OR SHAFTS - YEUNG, Chung Lai Wallace; CHAN, Hing Cheung; LAU, Darwin Tat Ming; KWOK, Chun Keung; CHENG, Ching Hei (2023)
The subject invention pertains to systems and methods for controlling an end-effector moving in three-dimensional space within long piles or shafts. Systems can include a fixed base platform, a cable-driven working platform, a cable-driven end-effector, a sensing system including draw wire sensors, gyroscopes, sonar sensors, and lidar, a control system in communication with the sensing system, and actuators for cables. The end-effector can be configurable to become a cable-driven parallel end-effector, a serially linked arm, a flexible end-effector or an air-lifting end-tool in cases of cleaning founding layers in bored pile shafts. The control system can be configurable to regulate the lengths of cables through actuators and modulate the positions and orientations of the working platform and the end-effector.